Environmental Flows in Nepal - An Evaluation of Current Practices and an Analysis of the Upper Trishuli-I Hydroelectric Project - Rijal, Narayan Hari; Alfredsen, Knut (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Environmental assessments and environmental flows are important components in modern hydropower development. Various methods employing a combination of hydrology, hydraulics, environmental assessment and ecology have been developed for analysing and setting environmental flows. In the developed countries, detailed assessments are being carried out for setting environmental flows whereas very little attention has been given to this topic in Nepal. However, this trend is changing in recent developments. We discuss current minimum flow practices for a number of hydropower projects in the planning, development and operation phases to observe minimum flows and environmental flow over time. Furthermore, we present an analysis of environmental flows for the Upper Trishuli-I Hydroelectric Project in Nepal that is currently in the planning phase. We base our conclusion using current flow assessment methodologies to study the effects of proposed minimum flows and possible changes to improve the effect of compensatory releases. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 17, July 2015